2020
DOI: 10.2514/1.j058517
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Drop Test of Composite Fuselage Section of a Regional Aircraft

Abstract: In this paper, a vertical drop test of a full composite fuselage section of a regional aircraft has been presented. This test was performed to investigate the structural response of a prototype of a composite fuselage section as well as the biomechanical response of the anthropomorphic dummies under a vertical crash loading condition. The research activity, carried out within the framework of Metodi di CERtificazione e Verifica Innovativi ed Avanzati (CERVIA) ‡ ‡ project, allowed collecting suitable amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 13 publications
(14 reference statements)
2
25
0
Order By: Relevance
“…In some studies [3] the main complexity of landing gear design is the identification of shock absorber characteristics, in order to match the airworthiness and aircraft requirements. Other studies [4,5] have demonstrated that the loads under impact and validation in non-linear conditions…”
Section: Main Landing Gear Trap Doors Outlinesmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies [3] the main complexity of landing gear design is the identification of shock absorber characteristics, in order to match the airworthiness and aircraft requirements. Other studies [4,5] have demonstrated that the loads under impact and validation in non-linear conditions…”
Section: Main Landing Gear Trap Doors Outlinesmentioning
confidence: 99%
“…In some studies [3] the main complexity of landing gear design is the identification of shock absorber characteristics, in order to match the airworthiness and aircraft requirements. Other studies [4,5] have demonstrated that the loads under impact and validation in non-linear conditions represent another challenge in landing gear design, in normal, and off nominal flight conditions, such as crash-landing ones. The design of the Racer trap doors requires stiffness considerations and the coupling effects of aerodynamic and inertial load with structure behavior [6].…”
Section: Main Landing Gear Trap Doors Outlinesmentioning
confidence: 99%
“…To verify its structural behavior under a dynamic load condition and to estimate its passive safety capabilities, the fuselage section was equipped with crash resistant data acquisition system (DAS), markers, anthropomorphic dummies (equipped with cell loads and accelerometers), accelerometers and strain gauges, and the entire test was filmed by two high-speed cameras, as presented in detail by the authors in [43].…”
Section: Drop Test Overviewmentioning
confidence: 99%
“…To monitor the dynamic structural response of the test article, 11 piezo-resistive accelerometers were installed as illustrated in Fig. 3d: three accelerometers in correspondence of the central bay of the cargo floor, seven accelerometers on the main floor, and the last one on the uppermost of the skin, in central position [43].…”
Section: Drop Test Overviewmentioning
confidence: 99%
See 1 more Smart Citation